2020
DOI: 10.3390/molecules25245830
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in the Pharmacological Profile of Copper Biological Active Complexes by Their Incorporation into Organic or Inorganic Matrix

Abstract: Every year, more Cu(II) complexes are proven to be biologically active species, but very few are developed as drugs or entered in clinical trials. This is due to their poor water solubility and lipophilicity, low stability as well as in vivo inactivation. The possibility to improve their pharmacological and/or oral administration profile by incorporation into inorganic or organic matrix was studied. Most of them are either physically encapsulated or conjugated to the matrix via a moiety able to coordinate Cu(I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 151 publications
(195 reference statements)
0
13
0
Order By: Relevance
“…As a result, there is a continuous search for new antitumor drugs with reduced side effects and lower toxicity. The Cu(II) systems represent beneficial species from this point of view, considering their reduced systemic toxicity [16]. Thus, several Cu(II) complexes were studied and proved to be as effective for melanoma treatment [18,29,[35][36][37][38][39][40][41][42][43]-some having, in addition, low toxicity on normal cells [18,29,[39][40][41][42][43].…”
Section: Biological Characterization 231 Cell Viability and Lactate Dehydrogenase Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, there is a continuous search for new antitumor drugs with reduced side effects and lower toxicity. The Cu(II) systems represent beneficial species from this point of view, considering their reduced systemic toxicity [16]. Thus, several Cu(II) complexes were studied and proved to be as effective for melanoma treatment [18,29,[35][36][37][38][39][40][41][42][43]-some having, in addition, low toxicity on normal cells [18,29,[39][40][41][42][43].…”
Section: Biological Characterization 231 Cell Viability and Lactate Dehydrogenase Assaysmentioning
confidence: 99%
“…Considering its biological potency, the tp scaffold is often used to develop biologically active complexes, with a net preference for Cu(II) against other metal ions. Copper(II) exhibits particular traits, such as borderline acid characteristics or stereochemical and oxidation state versatility [16]. Moreover, most of the Cu(II) complexes with tps were reported as having antiparasitic [17], antitumor, or antimicrobial activity [18].…”
Section: Introductionmentioning
confidence: 99%
“…The organic cytostatics used for melanoma chemotherapy generate severe side effects, including an increased risk of infection as well as resistance development. Hence, in a continuous search for new antitumor drugs with reduced side effects and lower toxicity, the Cu(II) complexes are preferred, considering their reduced systemic toxicity [ 18 ]. Thus, several Cu(II) species were developed as non-toxic compounds for healthy tissue but with high activity in melanoma cells [ 33 , 39 , 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…Studies concerning the complexes with such ions evidenced differences concerning their mechanisms of action. Thus, while Cu(II) manifests both redox [ 18 ] and hydrolytic [ 19 ] abilities in a biological environment, Zn(II) is primarily involved in promoting the hydrolytic reactions as a result of its strong Lewis-acid character [ 5 ]. Moreover, the interaction with biomolecules can be assisted by ligands that can control both the complex stability and their interaction with aromatic components of DNA and proteins through intercalation and/or weak interactions such as dipole–dipole, electrostatic, hydrogen bonds, or π–π stacking.…”
Section: Introductionmentioning
confidence: 99%
“…The application fields of such nanocomposites having a wide range of unique properties are quite diverse and include effective biomedical materials, inexpensive catalytic systems, optical nanosensors, and ecological biosorbents developing. Nevertheless, the usage of new copper-containing nanocomposites as an alternative to organic copper compounds in pharmacology and medicine is most promising [ 20 ]. Thus, it was shown that copper nanoparticles (CuNPs and CuO NPs) can be applied as antimicrobial, antifungal, anticancer, and anti-inflammatory agents as well as therapeutic agents for wound healing [ 8 , 21 ].…”
Section: Introductionmentioning
confidence: 99%